Антропоморфные божества ранне-земледельческих племен Южного Кавказа - Хидашели, M. Ш. (1984)
Ondaseli, M. Š., The anthropomorphic divinities of the early agricultural tribes of the South Caucasus; engl. Résumé S. 164